Backing Britain Campaign, 1968 (London, 1968)
1968 1961-70 "Backing Britain Campaign, 1968" [BW0204], 1968, Trades Union Congress I'm Backing Britain was a patriotic campaign started in December 1967, when five Surbiton secretaries volunteered to work an extra half an hour each day without pay in order to boost productivity, and urged others to do the same. There was an enormous media response and a campaign took off, becoming a nationwide movement within a week. As shown in this article from the Transport and General Workers' Union TGWU Record for February 1968, trade unions were suspicious of the campaign as an attempt to extend working hours and to hide inefficiency by management.